Cardiac (123)I-meta-iodobenzylguanidine (MIBG) uptake in dementia with Lewy bodies: comparison with Alzheimer's disease - Watanabe, H (BMJ Group, 2001)
Cardiac (123)I-meta-iodobenzylguanidine (MIBG) uptake was measured in 11 patients with dementia with Lewy bodies (DLB), 10 patients with Alzheimer's disease (AD), and 10 age matched control subjects. The severity of cognitive impairment and duration of symptoms in patients with DLB matched that in the patients with AD. The heart/mediastinum (H/M) ratio of MIBG uptake in the patients with AD was indistinguishable from that in the control subjects. However, the H/M ratio in all patients with DLB was significantly lower than that in the patients with AD and control subjects (p<0.001). These findings indicate that local myocardial sympathetic nerves are affected in DLB and that cardiac (123)I-MIBG scintigraphy may provide a means of differentiating DLB from AD.